Leg Press for Accelerating the Recovery of Patient with Reconstruction Anterior Cruciate Ligament Phase 3: A Case Report - Ferlita Oktabriani; Rifdatun Nabihah Roudhoh; Putri Febriani; Sharlyn Agatha Early; Hilya Hisanah (Universitas Negeri Surabaya, 2025)
Background: Anterior Cruciate Ligament (ACL) injuries are a major concern among athletes, often requiring surgical intervention followed by comprehensive rehabilitation. One of the recommended exercises during the strengthening phase (phase 3) of post-ACL reconstruction rehabilitation is the leg press Objectives: This case report aims to evaluate the effectiveness of leg press exercises as part of a rehabilitation program in a 22-year-old male football athlete following ACL reconstruction. Methods: The method involved progressive leg press training (30 kg, 3–4 times per week, 3 sets of 10–15 repetitions) and monitoring using Y Balance Test, agility t-test, and IKDC questionnaire Results: he results showed improvements in dynamic balance, agility, muscle strength, and overall knee function. These findings indicate that leg press exercise is effective in accelerating recovery, enhancing functional readiness, and reducing the risk of re-injury during the strengthening phase of ACL rehabilitation. Therefore, leg press exercises are recommended as part of a structured and individualized phase 3 rehabilitation program, particularly for athletes aiming to return to sports activities. Conclusion: Leg press exercise during phase 3 rehabilitation after ACL reconstruction effectively improves muscle strength, dynamic balance, agility, and knee function. Therefore, leg press can be recommended as a key component of a structured and progressive rehabilitation program to support functional recovery and return to sport.